Two-dimensional spintronic circuit architectures on large scale graphene. (May 2020) - Khokhriakov, Dmitrii; Karpiak, Bogdan; Hoque, Anamul Md.; Dash, Saroj P.
Abstract: Solid state electronics based on utilizing the electron spin degree of freedom for storing and processing information can pave the way for next-generation spin-based computing. However, the realization of spin communication between multiple devices in complex spin circuit geometries, essential for practical applications, is still lacking. Here, we demonstrate the spin current propagation in two-dimensional (2D) circuit architectures consisting of multiple devices and configurations using a large area CVD graphene on SiO2 /Si substrate at room temperature. Taking advantage of the significant spin transport distance reaching 34 μm in commercially available wafer-scale graphene grown on Cu foil, we demonstrate that the spin current can be effectively communicated between the magnetic memory elements in graphene channels within 2D circuits of Y-junction and hexa-arm architectures. We further show that by designing graphene channels and ferromagnetic elements at different geometrical angles, the symmetric and antisymmetric components of the Hanle spin precession signal can be remarkably controlled. These findings lay the foundation for the design of complex 2D spintronic circuits, which can be integrated into efficient electronics based on the transport of pure spin currents. Graphical abstract: Image 1